Conditions of subtidal forest of Lessonia trabeculata in Independencia island during "El Niño 1997-98" - Fernández, Ernesto (1999)
The changes of the dominant species features were evaluated in situ, in Lessonia trabeculata subtidal forest during "El Niño 1997-98", tor 14 months, at 3 m depth and the changes in vertical distribution of algae until18 m depth. The high sea temperature values of winter 1997 generated a firsl stress effecl on the species producing in many of them the loss of fronds and easily detachment from the substrate. A second stress effect occurred in summer of 1998, when fronds did not support the high sea temperature values reached, reducing covering in 50%. The tissues of the stipe, upper third, were rot and fall down in March. Both, the stipe length reduced from 150,2 to 31,3 cm and rhizoid diameter from 24,2 to 16,4 cm among February and July, the pressure of herbivorous contributed lo the reduction, and finally the density became worthless in August. The incapacity to regenerate new tissues and organs, the absent of recruitment, the way of disappearance, observed between 3 and 7 m depth in October 1998 made real the possibility of complete disappearance of the rest of L. trabeculata forest; located from 15 to 18 m depth, because the lack of fronds, and its presentation of similar characteristics previously described at minor depth.